Feeling of Well-being and Family Contacts in Community Elderly Residents - Okamoto, Kazushi (Nihon Rōnen Igakkai zasshi, 2000)
The aim of this study is to explore the factors associated with feelings of well-being in 683 community-dwelling elderly residents, aged 65 years and over using a self-administered questionnaire. The feeling of well-being was rated using a single question item constructed by The Japanese Association for Cerebro-cardiovascular Disease control (JACD), and then subjects were divided into two groups according to answer categories: happiness and unhappiness. There was no statistically significant difference in the proportion of subjects with happiness between males and females, or among age groups. Even when interaction among multiple factors were adjusted by logistic regression analysis, a high frequency of conversation with family was statistically significantly related to happiness, and the odds ratio of it was highest among all other factors. The odds ratio of high frequency of conversation with family was higher among the elderly aged 75 and over than among those aged 65-74. These results suggest that the construction of communication between the elderly and their family through conversation could contribute to feelings of well-being in the elderly.